Beckett Beyond the Normal - Kennedy, Seán (Edinburgh University Press, 2022)
Explores Beckett's artistic vision at the intersection of queer, disability and posthumanist studiesThe first volume to address norms and normalcy as an enduring target of Beckettian skepticismShifts the emphasis from generic talk of 'Other Becketts' to specific accounts of the queer, the disabling, the abnormalising aspects of the mature worksAbsorbs and transcends the philosophy/history binary that has shaped the last twenty yearsBrings Beckett Studies into the twenty-first century as the first intersectional volume to address queerness, disability and biopolitics togetherThis book examines why Beckett's writing is so queer, so disabled and disabling. Why did Beckett write so often about mental illness, disability, perversion? Why did he take such an interest in 'abnormals' and 'degenerates'? How did he reconceive 'the human' in the wake of Hitler and Stalin? Drawing on Beckett's voluminous archive, as well as his primary texts, the authors use psychoanalysis, queer theory, disability theory and biopolitics to push Beckett studies beyond the normal
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: Literary Studies; LITERARY CRITICISM / Feminist; Biopolitics in literature; Disabilities in literature; Sexual orientation in literature